Keterkaitan Diklat, Budaya Organisasi, dan Integritas Terhadap Kinerja Pegawai dengan Kompetensi Sebagai Variabel Mediasi (Studi Kasus Pada Badan Nasional Penanggulangan Terorisme) - Ramdani Rakasiwi, Gama; Bandawaty, Euis; Sunaryo; Waskito, Meindro (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2025)
This study examines both the direct and mediated effects of education and training, organizational culture, and integrity on employee performance, with competence positioned as an intervening variable at the National Counterterrorism Agency. A quantitative research design was employed, involving 130 employees as research respondents. The data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the support of SmartPLS version 4. The findings indicate that education and training, integrity, and competence have a positive and statistically significant direct effect on employee performance, whereas organizational culture does not demonstrate a significant direct influence. In addition, education and training, organizational culture, and integrity were found to significantly and positively affect employee competence. The mediation analysis further reveals that these three variables indirectly influence employee performance through competence. Competence fully mediates the relationship between education and training as well as integrity on employee performance, while partially mediating the relationship between organizational culture and employee performance.Overall, the results highlight that strengthening employee competence plays a critical role in enhancing the effectiveness of education and training, organizational culture, and integrity in improving employee performance within the National Counterterrorism Agency.